If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(x + -2) + 5x = 0 Reorder the terms: -4(-2 + x) + 5x = 0 (-2 * -4 + x * -4) + 5x = 0 (8 + -4x) + 5x = 0 Combine like terms: -4x + 5x = 1x 8 + 1x = 0 Solving 8 + 1x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + 1x = 0 + -8 Combine like terms: 8 + -8 = 0 0 + 1x = 0 + -8 1x = 0 + -8 Combine like terms: 0 + -8 = -8 1x = -8 Divide each side by '1'. x = -8 Simplifying x = -8
| 0.3x+7.8=11.4 | | (4x^2)-7x-36=0 | | 3x+6=x+5+5 | | -4m+5-3m-12= | | 107=6(3x+7)-7 | | 3x^2+5x+13=16 | | -7p-9=b-113 | | 7*20= | | 7-4(7-3)=23 | | -8x-40=2x | | -4x+5+9x-2andx=6 | | 2x+3(x-7)=-1 | | m=n+2p | | 5p-6=p+106 | | 5x+23=-2 | | 5b-4b=-2 | | 1x+8+4=17 | | -28.3y-82.3=y+1083.84 | | -4.3x=-10.75 | | -3(x+4)+2x=2(x-6)-3x | | 4x+17=-7 | | 2.4(1.3)x=9.6 | | 5c-2e+1=15 | | 13.5r+7.5=r-590 | | 3+(x-2)= | | 4(x+4)=2x+20 | | -3y+11+2x-y=1 | | x-(-22)=-6 | | -8.2p+7.2=p+267.56 | | -7x+3=-19 | | -3c+4=c+96 | | (24ab)(3)= |